Trend of Using Nurse Preceptor for Enrichment learning for the Learner - แจ่มจันทร์ ละเอียด; ภูมิศรีแก้ว สิริลักษณ์ (Journal of The Royal Thai Army Nurses, 2019)
The limited number of nurse instructor as well as the need of advanced nursing skills nurse for clinical teaching/training are professional problems. The nurse administrator should create nurse preceptor by Relationship-based care (RBC) plus accepted preceptor characteristics. Alternatively essential preceptor’s role is enculturation and compassion the learner being professional nurse. Buddhist principles for a qualities of a good teacher in the 7 characters : 1) lovable 2) respectable 3) adorable 4) being a counsellor 5) being a patient listener 6) able to deliver deep discourses or to treat profound subjects 7) not leading or spurring on to a useless end. These characters are appreciating for RBC in order to sharing between preceptor-learner continuing a good model of professional compassion and personal well-being.